In-laws and outlaws: lessons in research and friendship and a report from the archives - Gordon, Sarah Barringer, author; Utah State University Press, publisher (Colorado State University. Libraries, 2007)
I will talk about the three basic ingredients that have transformed my day job into a vocation: respect for the past, insight, generosity.--From page 1.
October, 20, 2005.
Keywords: Mormon Church -- Utah -- History; Marriage -- Utah -- History; Polygamy -- Utah -- History